2020
DOI: 10.3389/fpsyt.2020.579107
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in the Italian Population During Covid-19 Outbreak: A Snapshot on One Major Risk Factor for Depression and Anxiety

Abstract: Objectives: One of the largest clusters of Covid-19 infections was observed in Italy. The population was forced to home confinement, exposing individuals to increased risk for insomnia, which is, in turn, associated with depression and anxiety. Through a cross-sectional online survey targeting all Italian adult population (≥18 yrs), insomnia prevalence and its interactions with relevant factors were investigated.Methods: The survey was distributed from 1st April to 4th May 2020. We collected information on ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 46 publications
10
76
1
1
Order By: Relevance
“…This result confirms the conclusions of many longitudinal studies on the topic, in which people with sleep problems are more likely to develop depressive symptomatology [10][11][12]. Our findings are also consistent with evidence from international [54][55][56][57] and Italian [58][59][60][61] studies which observed a strong positive relationship between poor sleep quality and depression during the COVID-19 epidemic.…”
Section: Discussionsupporting
confidence: 91%
“…This result confirms the conclusions of many longitudinal studies on the topic, in which people with sleep problems are more likely to develop depressive symptomatology [10][11][12]. Our findings are also consistent with evidence from international [54][55][56][57] and Italian [58][59][60][61] studies which observed a strong positive relationship between poor sleep quality and depression during the COVID-19 epidemic.…”
Section: Discussionsupporting
confidence: 91%
“…Following article screening, a total of 51 studies were entered into the initial random effects model. Outlier analyses identified a total of ten studies 49 58 and these were subsequently excluded from the analysis (See Supplemental S2 for details of these studies including the 95% CI for each excluded effect size). Heterogeneity was reduced after excluding these studies (prior to exclusion I 2 = 77.9%, Q(52) = 235.11, p < 0.001, after exclusion I 2 = 60.2%, Q(42) = 105.5, p < 0.001) but remained substantial and significant.…”
Section: Resultsmentioning
confidence: 99%
“…Adults have a double risk of being newly diagnosed with a psychiatric disorder after the COVID-19 diagnosis 37 , and the most common psychiatric conditions presented were anxiety disorders, insomnia, and dementia. Sleep disturbances might contribute to the presentation of psychiatric disorders 38 . Prompt diagnosis and intervention of any neuropsychiatric care is recommended for all patients recovering from COVID-19.…”
Section: Discussionmentioning
confidence: 99%